Uji Laboratorium : Perencanaan High-Performance Water-Based Mud Untuk Mencegah Lost Circulation pada Trayek 17,5 inch Sumur Moon - Pebriana, Cindy; Fathan, Muhammad Rizqie; Ulfah, Baiq Maulinda (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Drilling mud plays an important role in 17 ½ inch track operations that often pass through reactive shale formations and fractured zones. This study was conducted to determine whether the High-Performance Water-Based Mud (HPWBM) formulation with KCl-Polymer and polyamine, as well as the addition of Lost Circulation Material (LCM) in the form of CaCO₃ and Fracseal, is capable of maintaining the rheological properties of mud under these conditions. The combination of CaCO₃ and Fracseal proved effective in reducing lost circulation and maintaining mud rheology. These results are in line with recent studies emphasizing the importance of using bridging materials and polymer additives in overcoming fracture rheology problems in intermediate trajectories. Laboratory test results showed a Mud Weight of 10.9 ppg, Plastic Viscosity of 29 cP, Yield Point of 37 lb/100 ft², and Low Shear Yield Point of 12 lb/100 ft². These parameters are within a good range to support cutting removal and fracture closure. The gel strength value of 14/28 lb/100 ft² and API Filtrate of 3.8 mL/30m also indicate that the mud is capable of forming a dense and stable filter cake.